Menguatnya Perkembangan Salafisme dan Dominasi Ekonomi Kelompok Bisnis Arab di Banyumas - Assidiq, Fajar (Civic Education Program, Universitas Negeri Semarang, 2019)
The development of electoral politics in Banyumas which led to the increasingly strong economic and political domination of Arab business groups influenced the development of Salafism especially in urban areas. This is due to the construction of sites spreading Salafism, such as foundations. Islamic boarding schools, mosques, mosques, schools and hospitals come from donations that they provide from the benefits of doing business in the fields of property construction, furniture, education and health. Banyumas as a